2013
DOI: 10.1093/cvr/cvt026
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in T-tubule and dyad structure in heart disease: challenges and opportunities for computational analyses

Abstract: Compelling recent experimental results make clear that sub-cellular structures are altered in ventricular myocytes during the development of heart failure, in both human samples and diverse experimental models. These alterations can include, but are not limited to, changes in the clusters of sarcoplasmic reticulum (SR) Ca(2+)-release channels, ryanodine receptors, and changes in the average distance between the cell membrane and ryanodine receptor clusters. In this review, we discuss the potential consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…11 Activation and gating of RyRs is dependent on local [Ca 2+ ], cytosolic and luminal, 12 and is further modulated through modification such as oxidation, nitrosylation, and phosphorylation. [13][14][15] Many proteins are involved; both kinases and phosphatases associate with the RyRs to form a macrocomplex.…”
mentioning
confidence: 99%
“…11 Activation and gating of RyRs is dependent on local [Ca 2+ ], cytosolic and luminal, 12 and is further modulated through modification such as oxidation, nitrosylation, and phosphorylation. [13][14][15] Many proteins are involved; both kinases and phosphatases associate with the RyRs to form a macrocomplex.…”
mentioning
confidence: 99%
“…In addition, the structural continuity in the oblique configuration opens the possibility of a higher degree of synchronization, either by virtue of holding two RyR2s together and facilitating CICR or by allosteric coupling. It has been suggested that the substructure of the CRU may be an important determinant of the kinetics of the Ca 2þ spark (14,15). Our work shows several possible RyR2 quaternary interactions within the CRU that could constitute a mechanism to fine-tune the SR Ca 2þ release kinetics during EC coupling.…”
Section: Physiological Implicationsmentioning
confidence: 99%
“…Walker et al (14) simulated the fine geometrical details of a CRU based on superresolution microscopy data and found that densely packed RyR2 arrays have the highest Ca 2þ spark fidelity. A more accurate structural detail of RyR2 clustering is necessary not only to model the canonical Ca 2þ spark as realistically as possible, but to make predictive models (15) that can accurately correlate alterations in specific parameters such as RyR2 cluster size, connectedness, and local SR volume (16) with the macroscopic defective Ca 2þ release observed in arrhythmia and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, JPH2 depletion in this mouse model also causes severe cardiomyopathy and heart failure 2,8 . T-tubule disruption is present in hearts with cardiomyopathy and heart failure 910 . Thus cardiomyopathy and heart failure confound the interpretation of the Jph2 knockdown phenotype with regard to its role in T-tubule maturation.…”
Section: Introductionmentioning
confidence: 99%